Insights Into Immunothrombosis: The Interplay Among Neutrophil Extracellular Trap, von Willebrand Factor, and ADAMTS13 - Yang, Junxian; Wu, Zhiwei; Long, Quan; Huang, Jiaqi; Hong, Tiantian; Liu, Wang; Lin, Jiangguo (Frontiers in Immunology, 2020)
Both neutrophil extracellular traps (NETs) and von Willebrand factor (VWF) are essential for thrombosis and inflammation. During these processes, a complex series of events, including endothelial activation, NET formation, VWF secretion, and blood cell adhesion, aggregation and activation, occurs in an ordered manner in the vasculature. The adhesive activity of VWF multimers is regulated by a specific metalloprotease ADAMTS13 (a disintegrin and metalloproteinase with thrombospondin type 1 motifs, member 13). Increasing evidence indicates that the interaction between NETs and VWF contributes to arterial and venous thrombosis as well as inflammation. Furthermore, contents released from activated neutrophils or NETs induce the reduction of ADAMTS13 activity, which may occur in both thrombotic microangiopathies (TMAs) and acute ischemic stroke (AIS). Recently, NET is considered as a driver of endothelial damage and immunothrombosis in COVID-19. In addition, the levels of VWF and ADAMTS13 can predict the mortality of COVID-19. In this review, we summarize the biological characteristics and interactions of NETs, VWF, and ADAMTS13, and discuss their roles in TMAs, AIS, and COVID-19. Targeting the NET-VWF axis may be a novel therapeutic strategy for inflammation-associated TMAs, AIS, and COVID-19.